2012
DOI: 10.1111/j.1756-8765.2012.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

To Name or to Describe: Shared Knowledge Affects Referential Form

Abstract: The notion of common ground is important for the production of referring expressions: In order for a referring expression to be felicitous, it has to be based on shared information. But determining what information is shared and what information is privileged may require gathering information from multiple sources, and constantly coordinating and updating them, which might be computationally too intensive to affect the earliest moments of production. Previous work has found that speakers produce overinformativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 30 publications
6
100
2
Order By: Relevance
“…Current models of the role of perspective in language production propose that the addressee's needs are only relevant at a delayed stage of processing (Horton & Keysar, 1996), or include the addressee's needs as one of many probabilistic constraints (Heller et al, 2012). The results of the present research paint a much more complex picture.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Current models of the role of perspective in language production propose that the addressee's needs are only relevant at a delayed stage of processing (Horton & Keysar, 1996), or include the addressee's needs as one of many probabilistic constraints (Heller et al, 2012). The results of the present research paint a much more complex picture.…”
Section: Discussionmentioning
confidence: 48%
“…Nadig and Sedivy (2002) found that even 5-to 6-year-old children, who are often considered egocentric (Epley, Morewedge & Keysar, 2004), showed successful use of common ground in both production and comprehension in situations in which the communicative goal was to request that the communicative partner pick up an object. Similarly, Heller et al (2012) found that while speakers sometimes referred to privileged information when making requests, they successfully distinguished privileged information from common ground in the same utterances. Other research showed that audience design is impaired in children with high-functioning autism, and is related to their language ability (Nadig, Vivanti & Ozonoff, 2009).…”
Section: Perspective In Production: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…According to collaborative models of discourse (e.g., Brennan & Clark, 1996;Hanna & Tanenhaus, 2004;Heller, Gorman, & Tanenhaus, 2012;Horton & Gerrig, 2002, 2005Lockridge & Brennan, 2002;Metzing & Brennan, 2003) While some discourse theories assume audience design, others claim that speakers may not necessarily construct their utterances completely with their listeners in mind but might have a more self-centred point of departure and only later adjust to the needs of their listeners (e.g., Horton & Keysar, 1996;Keysar, Barr, & Horton, 1998). A number of studies (e.g., Brown & Dell, 1987;Ferreira & Dell, 2000;Horton & Keysar, 1996;Wardlow Lane & Ferreira, 2008;Wardlow Lane et al, 2006) suggest that speakers produce language highly automatically using a production system that is less sensitive to the communicative needs of (e,g., Beattie, 1981;Clark, 1996; Jefferson, 1972).…”
Section: Is Anaphoric Reference Cooperative?mentioning
confidence: 99%
“…According to collaborative models of discourse (e.g., Brennan & Clark, 1996;Hanna & Tanenhaus, 2004;Heller, Gorman, & Tanenhaus, 2012;Horton & Gerrig, 2002, 2005Lockridge & Brennan, 2002;Metzing & Brennan, 2003) the information that interlocutors share or do not share at a particular point in the dialogue determines what kind of expressions speakers use for their addressees; that is, speakers are assumed to design their utterances with their addressees in mind and these partner-specific effects in communication emerge early in production processes (see Brennan & Hanna, 2009 for a review).…”
Section: Is Anaphoric Reference Cooperative?mentioning
confidence: 99%